Analysis of Land Uses In Iraqi Cities - Nabil T. Ismael; Areej Muhy Abdulwahab (Wasit Journal of Engineering Sciences)
Abstract—Land use plans in Iraqi cities are traditional and don’t seek to be sustainable and therefore could have negative impacts on the city from the environmental, economic, social and urban aspects. Consequently, the research aims to analyze the current and future of the land use for a set of Iraqi cities to reach the indicators of the gap between traditional and sustainable plans when planning for land uses.